Ranibizumab in the treatment of choroidal neovascularization on the border of an inferior staphyloma associated with tilted disc syndrome - Luis Arias (Dove Medical Press, 2010)
Luis Arias1,2, Jordi Monés21Hospital Universitari de Bellvitge, L’Hospitalet de Llobregat, Barcelona; 2Institut de la Màcula i de la Retina, Centro Médico Teknon, BarcelonaPurpose: To describe a case of choroidal neovascularization (CNV) on the border of an inferior staphyloma associated with tilted disc syndrome treated with intravitreal ranibizumab.Patients: Observational case report.Methods: A patient with CNV on the border of an inferior staphyloma associated with tilted disc syndrome was imaged using fluorescein angiography, autofluorescence and spectral domain optical coherence tomography, and treated with intravitreal injections of ranibizumab. Results: The patient received 3 ranibizumab injections during the 9-month follow-up. The visual acuity improved from 20/40 to 20/32 and the foveal thickness reduced from 470 microns to 248 microns. The angiograms showed resolution of leakage associated with CNV. There were no adverse events.Conclusion: Intravitreal ranibizumab is an efficacious and safe treatment in the management of choroidal neovascularization on the border of an inferior staphyloma associated with tilted disc syndrome.Keywords: intravitreal ranibizumab, choroidal neovascularization, tilted disc syndrome, inferior staphyloma